Preliminary Study on Antimalarial Agent From Indonesian Swietenia Mahagoni and Kibatalia Arborea - Triatmoko, Bawon; Pratoko, Dwi Koko; Pratama, Antonius Nugraha Widhi; Purnomo, Yoshinta Debi; Laksono, Tinton Agung; Nugraha, Ari Satia (Proceedings of the International Conference on Green Technology; Vol 10 (2019): Proceeding of International Conference on Green Technology, 2019)
Malaria is a global public health concern due to the increase of resistance to antimalarials, therefore the search for new antimalarials is of importance. This study was conducted to explore the antimalarial activity of Swietenia mahagoni and Kibatalia arborea in the form of crude methanolic extract. The plants were collected from Klaten-Central Java, and Batu-East Java, Indonesia. In vitro antimalarial assay was done against Plasmodium falciparum. Phytochemical studies were done chemically using Dragendorff’s reagent and spectroscopically using the 1H-NMR technique. Results show that the extract indicated positive antimalarial activity. Preliminary chemotype studies revealed the extract constitutes alkaloid compounds in which proton NMR indicated a typical aromatic alkaloid molecular structure. In conclusion, S. mahagoni K. arborea are potential for an antimalarial agent and further studies are necessary to obtain the bioactive compounds responsible for the claimed activity.